Measuring the uptake of clinic-based HIV treatment and prevention services following HIV testing and referral at private pharmacies in Kenya - Victor Omollo; Stephanie D. Roche; Shengruo Zhang; Magdalene Asewe; Bernard K. Rono; Benn Kwach; Greshon Rota; Patricia Ong’wen; Kendall Harkey; Josephine Odoyo; Daniel Were; Kenneth Ngure; et al. (BMC Health Services Research)
Abstract Background Despite their ubiquity across sub-Saharan Africa, private pharmacies are underutilized for HIV service delivery beyond the sale of HIV self-test kits. To understand what uptake of HIV prevention and treatment services might look like if private pharmacies offered clients free HIV self-testing and referral to clinic-based HIV services, we conducted a pilot study in Kenya. Methods At 20 private pharmacies in Kisumu County, Kenya, pharmacy clients (≥ 18 years) purchasing sexual health-related products (e.g., contraception) were offered free HIV testing. Based on their test result and recent self-reported behaviors associated with HIV risk, clients were encouraged to consider pre-exposure prophylaxis (PrEP), post-exposure prophylaxis (PEP), or antiretroviral therapy (ART) initiation, informed where they could access free services, and issued a referral. We called clients three months after study completion to see if they had initiated the recommended service. Among clients who reported PrEP referral, we used Poisson regression models to examine characteristics associated with PrEP initiation and calculated adjusted prevalence ratios (aPRs). Results From March to June 2022, 1500 pharmacy clients completed HIV testing and were referred to clinic-based HIV services; in October 2022, 1178 (79%) were reached and meet our criteria for follow-up. Among those reached, the majority (63%, 742/1178) were women, the median age was 26 years (IQR 22–31), and few (4%, 51/1178) reported any prior PrEP use. At the pharmacy, most clients (96%, 1136/1178) tested HIV-negative and reported PrEP (95%, 1122/1178) or PEP (1%, 14/1178) referral; the remainder (4%, 42/1178) tested HIV-positive and reported ART referral. The uptake of ART (90%, 38/42) and PEP (86%, 12/14) among clients referred was high. The uptake of PrEP was only 9% (101/1122) among those referred and prior PrEP use was the only characteristic significantly associated with initiation (aPR 2.45, 95% confidence interval 1.19 to 5.07). Conclusions Although offering free HIV testing at private pharmacies led to the identification and referral of clients who could benefit from HIV services, additional interventions (e.g., incentives, patient navigators) may be needed to support PrEP referral follow-through. Alternatively, new delivery models that circumvent the need for referrals, such as same-day PrEP initiation at pharmacies, should be considered.